COMPARATIVE STUDY BETWEEN MANUAL VACUUM ASPIRATION (MVA) VERSUS DILATATION AND CURETTAGE (D&C) IN FIRST TRIMESTER MISCARRIAGE (Journal of Medical & Health Sciences Review, 2025)
Background:  Miscarriage is a serious health problem across all over the world which is affecting 10-20% of pregnancies. The aim of this was study to compare the efficacy of manual vacuum aspiration with dilatation and curettage in first trimester miscarriages.Methods: It was non-probability consecutive study of 108 women ages between 20 to 35 years, presenting to first trimester with missed miscarriage and gestational age